Physicochemical, microbiological, and sensorial properties of chickpea yogurt analogue produced with different types of stabilizers - Mohd Fazla, Sofia Nadhirah; Marzlan, Anis Asyila; Meor Hussin, Anis Shobirin; Abd Rahim, Muhamad Hafiz; Madzuki, Iffah Nadhira; Mohsin, Aliah Zannierah (Springer Science and Business Media LLC, 2023)
There is a growing need for plant-based yogurts analogue that meet consumer demands in terms of texture and sensory qualities. Stabilizers are crucial in plant-based yogurt's physical properties which develop a thicker and creamier texture mimicking dairy yogurt. The addition of stabilizers helps to prevent syneresis. Thus, the study aims to evaluate the effect of pectin, corn starch, and locust bean gum (LBG) at different ratios on the physical, chemical, microbiological, and sensory properties of chickpea yogurts analogue (CYA). The concentration of stabilizer significantly influenced (p < 0.05) the proximate compositions, physicochemical and textural properties, and cell viability. A significant increase (p < 0.05) was observed in yogurt viscosity with the addition of corn starch and LBG at 1.0%. Firmness and consistency were improved in samples supplemented with 1.0% corn starch and commercial stabilizer. The sensory evaluation indicated that adding LBG at the ratio of 0.5% generated better preference among panelists in the appearance, color, and texture aspects despite commercial CYA showing significantly higher overall acceptability (p < 0.05) than other samples. The stabilizer's behavior significantly impacts the features of CYA which with 0.5% LBG received high consumer acceptance, which proves a good potential for CYA to be on the same shelf with other commercial yogurts analogue in the market.